PROGRAM BELAJAR DI BULAN RAMADHAN DALAM MENUMBUHKAN KARAKTER POSITIF SISWA MI - Ahmad Sihabuddin Mubarok; Anlianna (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
The purpose of this article is to increase our understanding of how carrying out activities during the month of Ramadan can improve character education; the influence of the activity itself on character education; and factors that support and hinder the implementation of these activities in fostering character education. Data obtained through literature and field research supports the descriptive analysis method used in this research. Researchers also use observation, interviews, documentation, and questionnaires to collect data. Then, all the data that has been collected is processed through various steps, starting with data reduction (retrieving the necessary data), data display (displaying the data), and data verification (generating conclusions). Researchers used double-checking techniques, persistent observation, and triangulation to test the validity of the data. The research results show that the activities carried out during the month of Ramadan are very varied and diverse. Keywords: Character education, Ramadan activities, positive character.